2016
DOI: 10.1080/13880209.2016.1178779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulberry leaf (Folium Mori) on insulin resistance via IRS-1/PI3K/Glut-4 signalling pathway in type 2 diabetes mellitus rats

Abstract: (2016) Effect of mulberry leaf (Folium Mori) on insulin resistance via IRS-1/PI3K/Glut-4 signalling pathway in type 2 diabetes mellitus rats, Pharmaceutical Biology, 54:11, 2685-2691, DOI: 10.1080/13880209.2016 Context: Folium Mori, the leaf of Morus alba L. (Moraceae), has been used in traditional Chinese medicine (TCM) for treating diabetes. However, it is unclear which components in the mulberry leaf are effective for the treatment of type 2 diabetes mellitus (T2DM). Objective: To investigate the flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 29 publications
4
56
0
Order By: Relevance
“…In the present study, it was observed that NF-κB expression levels were increased in type 2 DM rats and downregulated by Tan-IIA treatment. A previous report demonstrated that targeting of the IRS-1 pathway may regulate insulin resistance in type 2 DM rats (31). In the present study, Tan-IIA elevated expression levels of IRS-1 in renal cells in type 2 DM rats.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, it was observed that NF-κB expression levels were increased in type 2 DM rats and downregulated by Tan-IIA treatment. A previous report demonstrated that targeting of the IRS-1 pathway may regulate insulin resistance in type 2 DM rats (31). In the present study, Tan-IIA elevated expression levels of IRS-1 in renal cells in type 2 DM rats.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, rosiglitazone was also confirmed to significantly reduced TC and TG levels. The past study ever showed that rosiglitazone ameliorated dyslipidemia (Cai et al 2016), which was in line with the results of this study. The data suggest that ZDQ improved dyslipidemia in type 2 diabetic rats in addition to anti-insulin resistant actions.…”
Section: Zdq Reduced Plasma Tc and Tg In Type 2 Diabetic Ratssupporting
confidence: 80%
“…In the present study, administration of chicory inulin reversed T2DM‐induced down‐regulation of p‐IRS in the skeletal muscle and the liver, suggesting that chicory inulin could restore insulin signaling in T2DM rats. JNK and P38 MAPK are two stress‐activated kinases that have been found to be highly activated in diabetic conditions , whereas deactivation of P38 and JNK could elevate p‐IRS level, improve plasma insulin level and restore glucose homeostasis in diabetic rats . It was shown that JNK or P38 inhibitor could partially reverse oleylethanolamide‐induced impairment of glucose uptake in adipocytes .…”
Section: Discussionmentioning
confidence: 99%